Understanding the Changes to the Patient’s Bill of Rights as a Result of the Affordable Care Act - Deanna Andrews; Martie Gillen (EDIS)
The Affordable Care Act is a legislative act that has provided individuals and families more choices related to healthcare insurances. It offers consumers new protections and benefits by creating a more defined Patient’s Bill of Rights. This 2-page fact sheet was written by Deanna Andrews and Martie Gillen, and published by the UF Department of Family, Youth and Community Sciences, May 2014.